A son called Gabriel - McNicholl, Damian (London Legend Press Ltd, 2008)
Gabriel Harkin is the eldest of four children in a working-class family in 1960s Northern Ireland, struggling through a loving, if often brutal, childhood. In the staunchly Catholic community to which Gabriel belongs, the strict rules for belief and behavior are clear. But his upbringing is marked by constant bullying by peers who prey on his gentle nature and the constant battle to earn the love and respect of his father. Even as he strives to be the perfect picture of young Irish boyhood, he is undermined at every turn by his true feelings. As political clashes and violence take place across the country, Gabriel must face his own inner turmoil.